Cátaros en los Pirineos. Movilidades heréticas a través de un espacio fronterizo en construcción (siglos xii-xiv) - Carles Gascón Chopo (Les Cahiers de Framespa)
The close human, economic, and cultural ties between the two sides of the Pyrenees throughout the 12th century channeled the penetration of Catharism into Catalonia, reaching its maximum expression in the southern Pyrenees during the first third of 13th century. The expansion of Occitan Catharism in Catalan lands occurred without great difficulty, despite its limited scope, through some itinerant preachers who had no major problems relating to local communities. The introduction of the Court of the Holy Inquisition in the Crown of Aragon and its proven effectiveness in the persecution of heresy contributed to its rapid decline, parallel to what happened on the north side of the Pyrenees. However, the organization of the Inquisition by ecclesiastical provinces and the parallel implementation of the Pyrenean state border through the Treaty of Corbeil (1258), disturbed this inquisitorial action to a certain extent and enabled the existence of a relatively safe Occitan exile in the Crown of Aragon, as recorded in a very detailed way in the inquisitorial record of Jacques Fournier, Bishop of Pamiers, in the early 14th century. This article proposes the analysis of the effects of the consolidation of this Pyrenean border on the dynamics of Catharism through the mountain range in the 12th, 13th, and 14th centuries.